المسرح في الوطن العربي فن أصيل أم وافد جديد؟ - بختي صورية (UNIVERSITE MSILA, 2022)
يعد المسرح فنٌ قديمٌ ارتبط ظهوره بالطقوس الدينية إلاّ أنه ما لبث أن أصبح فنا قائما بذاته، ويذهب معظم الكتاب الدارسين أن بدايته كانت عند الاغريق القدامى، وهذا لا يعني أنه لم يكن موجودا عند الشعوب الأخرى، والعرب على غرار هذه الشعوب لها تاريخ حافل بالتراث والتقاليد مثل طقوس العبادات والحكواتي وخيال الظل والقراقوز.. الخ. وعمل الباحثون على استخراج مختلف ظواهر الفرجة الشعبية والوقوف عند العناصر الدرامية التي تحتويها محاولين بذلك تفنيد فكرة أن العرب لم يعرفوا فن المسرح وتعزيز الاتجاه نحو تأثير المسرح العربي انطلاقا من تلك الظواهر المسرحية والسؤال الذي يطرح نفسه هل تلك الظواهر والأشكال المسرحية، تصلح أن تكون أساسا لإقامة مسرح عربي متميز؟ Theatre is an ancient art whose appearance has been associated with religious rituals, but soon became a stand-alone art, and most scholars argue that it began with the ancient Greeks, which does not mean that it did not exist among other peoples, and Arabs like these peoples have a history of heritage and traditions such as rituals of worship, storytellers, shadow fiction and qaraquz. etc. The researchers worked to extract the various phenomena of popular watching and stand by the dramatic elements contained in them, thus trying to refute the idea that Arabs did not know the art of theater and promote the trend towards the influence of Arab theater based on those theatrical phenomena and the question that arises is whether these phenomena and theatrical forms can serve as the basis for the establishment of a distinct Arab theater?
Keywords: المسرح العربي ; الظواهر المسرحية ; التراث ; Arab Theater ; Theatrical phenomena ; Heritage